1989
DOI: 10.1007/bf01541674
|View full text |Cite
|
Sign up to set email alerts
|

Pornography and community standards in Hawaii: Comparisons with other states

Abstract: This first statewide study, using random phone interviews, found a community standard for the acceptance of sexually explicit material. Research shows respondents are conservative in voting for the death penalty and against the legalization of those drugs presently illegal, even marijuana. In other regards, Hawaiians think abortion should be only for the women to decide and that adults should not be denied access to explicit material that shows other adults in consensual sexual acts. The majority of those inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The nding of little difference in responses between age groups contrasts with several earlier studies where younger people have been reported as nding sexually explicit material more acceptable than older people (Barnett & Thomson, 1996;ITC, 1996;Diamond & Dennemiller, 1989;Merritt et al, 1975). Barnett & Thomson (1996) reported that age was the strongest factor in uencing responses to sexually explicit material.…”
Section: Discussionmentioning
confidence: 56%
“…The nding of little difference in responses between age groups contrasts with several earlier studies where younger people have been reported as nding sexually explicit material more acceptable than older people (Barnett & Thomson, 1996;ITC, 1996;Diamond & Dennemiller, 1989;Merritt et al, 1975). Barnett & Thomson (1996) reported that age was the strongest factor in uencing responses to sexually explicit material.…”
Section: Discussionmentioning
confidence: 56%
“…Our measure of experience with pornographic materials is limited compared to those used by others who have designed specific surveys around the topic, typically with a single-community or single-state sample rather than a national sample (Diamond and Dannemiller 1989;Lottes, Weinberg, Weller 1993). Our reliance on the GSS means that we do not have access to an array of variables that allows us to make fine-tuned distinctions in the type of pornography that the individual has experienced.…”
Section: Methodsmentioning
confidence: 99%
“…We also incorporate other traits and attitudinal predispositions that may be expected to account for variation in acceptance of causal attributions concerning pornography and rape. Standard demographic variables such as age, education, and income level, as well as social and political orientations such as political ideology and religiosity, have been linked to attitudes on pornography in previous research, typically with more favorable views of pornography associated with youth, higher levels of education and income, less religiosity, and greater political liberalism (Diamond and Dannemiller 1989;"Dirty Pictures" 1987;Gunther 1995;Lottes, Weinberg, and Weller 1993;Wilson and Abelson 1973;Wu and McCaghy 1993). 1 Other literature, focusing on attributions involving one's own performance or behavior, suggests a more contingent view of gender differences-i.e., that women are more likely to identify external causes for success and internal causes for failure, while the reverse is true for men (Scott 1997;Ashkanasy 1994;Top 1991).…”
Section: Individual Characteristics: Attitudinalmentioning
confidence: 99%
“…Robinson et al 1999;ITC 1995 ;Rosser et al 1995;Docherty et al 1988;Allen 1987;Diamond andDennemiller 1989, Merritt, Gerstl, andLoscioto 1975).…”
Section: Sex Education 383mentioning
confidence: 96%